2014
DOI: 10.1111/ggi.12206
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness is associated with low skeletal muscle mass in Japanese community‐dwelling older adults

Abstract: Aim:To examine whether arterial stiffness, measured by the cardio-ankle vascular index (CAVI), is associated with skeletal muscle mass index (SMI) in Japanese community-dwelling older adults.Methods: Data were collected from 175 participants through questionnaires and specific tests; the data included demographic, lifestyle and health characteristics, body mass index (BMI), and body composition features determined by the bioelectrical impedance analysis, ankle-brachial index, the Mini-Nutritional Assessment, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 28 publications
3
65
0
1
Order By: Relevance
“…Association b e t w e e n UCr and high baPWV measured by BIA was inversely associated with the radial augmentation index in men [20]. Sampaio et al also found an association between a low skeletal muscle mass index by BIA and a cardio-ankle vascular index in community-dwelling older adults [21]. Only a few studies have assessed the relationship between muscle mass and arterial stiffness in CKD patients, and those studies have only considered patients on hemodialysis (HD).…”
Section: Discussionmentioning
confidence: 99%
“…Association b e t w e e n UCr and high baPWV measured by BIA was inversely associated with the radial augmentation index in men [20]. Sampaio et al also found an association between a low skeletal muscle mass index by BIA and a cardio-ankle vascular index in community-dwelling older adults [21]. Only a few studies have assessed the relationship between muscle mass and arterial stiffness in CKD patients, and those studies have only considered patients on hemodialysis (HD).…”
Section: Discussionmentioning
confidence: 99%
“…Investigation into the risk factors and associated factors of muscle mass decline has been ongoing for several decades. Many of the risk factors assessed for declines in muscle mass, summarized in Table , include chronic conditions, such as diabetes, heart disease and hyperlipidemia; arterial stiffness, malnutrition and hematological factors . Several hematological components have been linked to the loss of muscle mass, such as high creatinine, and high albumin concentration had protective effects .…”
Section: Risk Factors Of Sarcopenia Componentsmentioning
confidence: 99%
“…Sarcopenia, the age‐related loss of muscle mass, is defined by reduced appendicular skeletal muscle mass (ASM) relative to height (ASMI) . Sarcopenia and low‐ASMI (pre‐sarcopenia) are associated with increased arterial stiffness (pulse wave velocity, PWV) and wave reflection (augmentation index, AIx) . Arterial stiffening contributes to higher prevalence of systolic hypertension in postmenopausal women via increased wave reflection, which is a major determinant of aortic pulse pressure (aPP) .…”
Section: Participant Characteristics At Baseline In the Low‐asmi And mentioning
confidence: 99%